Fungal functional ecology: bringing a trait‐based approach to plant‐associated fungi. (25th November 2019) - Zanne, Amy E.; Abarenkov, Kessy; Afkhami, Michelle E.; Aguilar‐Trigueros, Carlos A.; Bates, Scott; Bhatnagar, Jennifer M.; Busby, Posy E.; Christian, Natalie; Cornwell, William K.; Crowther, Thomas W.; Flores‐Moreno, Habacuc; Floudas, Dimitrios; et al.
ABSTRACT: Fungi play many essential roles in ecosystems. They facilitate plant access to nutrients and water, serve as decay agents that cycle carbon and nutrients through the soil, water and atmosphere, and are major regulators of macro‐organismal populations. Although technological advances are improving the detection and identification of fungi, there still exist key gaps in our ecological knowledge of this kingdom, especially related to function. Trait‐based approaches have been instrumental in strengthening our understanding of plant functional ecology and, as such, provide excellent models for deepening our understanding of fungal functional ecology in ways that complement insights gained from traditional and ‐omics‐based techniques. In this review, we synthesize current knowledge of fungal functional ecology, taxonomy and systematics and introduce a novel database of fungal functional traits (Fun Fun ). Fun Fun is built to interface with other databases to explore and predict how fungal functional diversity varies by taxonomy, guild, and other evolutionary or ecological grouping variables. To highlight how a quantitative trait‐based approach can provide new insights, we describe multiple targeted examples and end by suggesting next steps in the rapidly growing field of fungal functional ecology.